(untitled) (Diametros, 2006)
The article presents various themes taken from Kant’s pre-critical philosophy in the area of the philosophy of nature, including many original hypotheses and arguments that are infrequently used in his critical philosophy and are therefore less known. The author presents the innovative hypothesis connecting the three-dimensional character of space with the law of gravitation, found in Kant’s first dissertation Gedanken von der wahren Schätzung der lebendigen Kräfte und Beurteilung der Beweise from 1747. He discusses the work entitled Allgemeine Naturgeschichte und Theorie des Himmels, which contains Kant’s famous hypothesis about the genesis of the solar system. He also presents the so-called hand argument (found in Von dem ersten Grunde des Unterschiedes der Gegenden im Raume), together with a short discussion.